2013
DOI: 10.1111/ane.12197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral contraceptives on lamotrigine levels depends on comedication

Abstract: Adding OCs to LTG monotherapy or the combination LTG-CBZ significantly increased the LTG clearance and thus reduced LTG serum levels. In the combination LTG-CBZ, OCs had a non-significant effect on CBZ clearance. No significant influence of cyclic OC use on LTG or VPA clearance was found when these AEDs were used in combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…However, if she is on a concomitant hormonal contraceptive that includes an estrogen, then her dose can often be adjusted lower when the hormonal contraceptive is stopped if she is on LTG, VPA, and probably OXC. LTG clearance is increased not only in pregnancy with the endogenous rise in sex steroid hormones, but clearance is also approximately 2-fold higher with exogenous administration of estrogens via combined oral contraceptive pills and other contraceptives that contains estrogens (e.g., patch, vaginal ring) [46][47][48][49][50]. Similar but more modest effects have been shown for VPA [51]; VPA concentrations were 23 % lower in the VPA plus combined oral contraceptive group than the VPA alone group.…”
Section: Establishing Individual Aed Target Concentrationsmentioning
confidence: 63%
“…However, if she is on a concomitant hormonal contraceptive that includes an estrogen, then her dose can often be adjusted lower when the hormonal contraceptive is stopped if she is on LTG, VPA, and probably OXC. LTG clearance is increased not only in pregnancy with the endogenous rise in sex steroid hormones, but clearance is also approximately 2-fold higher with exogenous administration of estrogens via combined oral contraceptive pills and other contraceptives that contains estrogens (e.g., patch, vaginal ring) [46][47][48][49][50]. Similar but more modest effects have been shown for VPA [51]; VPA concentrations were 23 % lower in the VPA plus combined oral contraceptive group than the VPA alone group.…”
Section: Establishing Individual Aed Target Concentrationsmentioning
confidence: 63%
“…Previous published studies showed that various factors such as weight , age , pregnancy , smoking , blood urea nitrogen : serum creatinine ratio , race , LTG daily dose [31], oral contraceptives and use of concurrent AEDs influence LTG plasma concentrations. Additionally, genetic polymorphisms in genes encoding drug‐metabolizing enzymes UGT1A4 , UGT2B7 and ABCB1 transporter [21] were also suggested to contribute to the IIV of LTG CL.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in patients taking valproic acid, the half‐life of LTG is substantially prolonged [10]. LTG has been extensively evaluated in pregnancy and in women taking oral contraceptives because of the reported decrease in serum LTG concentrations . LTG glucuronidation appears to be induced with estradiol [16].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [66] developed a statistical population pharmacokinetic model and showed that pharmacogenetic allelic forms and oestrogen levels during pregnancy are important covariates that influence the lamotrigine concentrations during pregnancy. Wegner et al [67] demonstrated in a clinical drug-drug interaction study that oral contraceptives influence the lamotrigine concentrations and proposed that changes in LTG clearance were due to UGT1A4 induction similar to that seen during pregnancy. The PBPK modelling strategy adopted by us includes the effect of oestrogen hormones during pregnancy but currently excludes the PK variability that may occur due to UGT1A4 genetic polymorphism.…”
Section: Discussionmentioning
confidence: 99%